2018
DOI: 10.2147/idr.s159447
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after initial treatment of methicillin-resistant <em>Staphylococcus aureus</em> infections

Abstract: ObjectiveTo evaluate the clinical outcomes associated with anti-methicillin-resistant Staphylococcus aureus (MRSA) antimicrobials.MethodsWe reviewed a prospective database of 247 consecutive patients with clinically and microbiologically confirmed MRSA infections, hospitalized in 7 Japanese hospitals between April 2014 and March 2015, and treated with anti-MRSA pharmaceuticals. Survival was measured at 30 days. We examined the relationships between initial antimicrobial administered and survival and organ toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…1a). Of these, 86 articles were further examined in detail, and finally, eight studies [18][19][20][21][22][23][24][25] were included in the meta-analysis for effectiveness evaluation, 16 studies [9,20,[26][27][28][29][30][31][32][33][34][35][36][37][38][39] were included in the meta-analysis for safety evaluation, and one study was included in both analyses (Kullar 2011).…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a). Of these, 86 articles were further examined in detail, and finally, eight studies [18][19][20][21][22][23][24][25] were included in the meta-analysis for effectiveness evaluation, 16 studies [9,20,[26][27][28][29][30][31][32][33][34][35][36][37][38][39] were included in the meta-analysis for safety evaluation, and one study was included in both analyses (Kullar 2011).…”
Section: Search Resultsmentioning
confidence: 99%
“… Fujii 2013 [ 29 ] Retrospective Japan 2011 > 18 Median (range), SD: 64 (21–88), 14.2 Percentage of MRSA is not available. Highest Trough levels determined 3 days after the initiation of vancomycin therapy Ley 2013 [ 30 ] Retrospective America 2006–2010 ≥18 Mean ± SD: 50 ± 22.6 Percentage of MRSA is not available: Trauma. Trough levels drawn 1 h prior to the subsequent dose Barriere 2014 [ 31 ] Retrospective 38 countries 2005–2007 ≥18 Mean ± SD: 64.7 ± 16.2 MRSA pneumonia (78%): S. aureus nosocomial pneumonia, multilobar pneumonia, bacteremia.…”
Section: Resultsmentioning
confidence: 99%
“…For the evaluation of different PK monitoring strategies, two studies assessing effectiveness ( n = 326) [ 18 , 19 ] and four studies assessing safety ( n = 1902) [ 18 , 19 , 20 , 21 ] were selected for meta-analyses. For the evaluation of vancomycin trough concentrations, effectiveness was assessed at a cut-off of 10 (two studies, n = 393) [ 22 , 23 ] or 15 µg/mL (eight studies, n = 849) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], and safety was assessed through a comparison of 10–15 and <10 µg/mL (14 studies, n = 1637) [ 22 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], through a comparison of 15–20 and 10–15 µg/mL (12 studies, n = 1211) [ 22 , 30 , 31 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], and through a comparison of ≥20 and 15–20 µg/mL (14 studies, n = 1127) [ 22 , 30 ...…”
Section: Methodsmentioning
confidence: 99%
“…Finally, eight articles from three databases that met the inclusion criteria were analysed for this meta-analysis, involving 634 patients who had received teicoplanin (Figure 1). [14][15][16][17][18][19][20][21] Among the eight articles, 15 datasets were constructed. We confirmed that the same patients were not duplicated in multiple subgroups.…”
Section: Summary Of Database Searchmentioning
confidence: 99%